Challenges optimizing the after visit summary. (December 2018) - Federman, Alex; Sarzynski, Erin; Brach, Cindy; Francaviglia, Paul; Jacques, Jessica; Jandorf, Lina; Munoz, Angela Sanchez; Wolf, Michael; Kannry, Joseph
Highlights: Health IT experts report challenges making the AVS in EHR platforms easier to understand. Our effort to implement an AVS that used health literacy strategies met with similar challenges. AVS customizations are frequently erased following EHR software updates. Abstract: Background: The after visit summary (AVS) is a paper or electronic document given to patients after a medical appointment, which is intended to summarize patients' health and guide future care, including self-management tasks. Objective: To describe experiences of health systems implementing a redesigned outpatient AVS in commercially available electronic health record (EHR) systems to inform future optimization. Materials and Methods: We conducted semi-structured interviews with information technology and clinical leaders at 12 hospital and community-based healthcare institutions across the continental United States focusing on the process of AVS redesign and implementation. We also report our experience implementing a redesigned AVS in the Epic EHR at the Mount Sinai Hospital in New York City, NY. Results: Health systems experienced many challenges implementing the redesigned AVS. While many IT leaders noted that the redesigned AVS is easier to understand and the document is better organized, they claim the effort is time-consuming, Epic system upgrades render AVS modifications non-functional, and primary care and specialty practices have different needs in regards to content and formatting. Our team was able to modify the document by changing the order of print groups, modifying the font size, bolding section headers, and inserting page breaks. Similar to other health systems, our team found that it is difficult to achieve some desired features due to limitations in the EHR platform. Conclusion: Health IT leaders view the AVS as a valuable source of information for patients. However, limitations to AVS modifications in EHR systems present challenges to optimizing the tool. EHR vendors should incorporate learning from healthcare systems innovation efforts and consider building more flexibility into their product development.